1993
DOI: 10.1001/archinte.153.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella aortitis. A report of a successfully treated case with a comprehensive review of the literature

Abstract: A successfully treated case of Salmonella infection of the thoracic aorta is described. Salmonella enteritidis was isolated from blood cultures and from operative cultures of the aorta. Computed tomography suggested the site of infection, and the resection of the thoracic aortic aneurysm with specific antibiotic therapy resulted in a satisfactory outcome. Although once invariably fatal, improved diagnostic roentgenographic techniques, more potent antibiotics, and surgical advances have resulted in at least 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 70 publications
0
76
0
Order By: Relevance
“…Nowadays, the use of the term "mycotic aneurysm" implies a wide spectrum of disease entities including all cases of true or pseudoaneurysms. Most of the patients with mycotic aneurysm due to Salmonella have preexisting atherosclerotic disease at the site of subsequently infected aneurysm (40,105). In a series of patients with bacteremia due to Salmonella, 25% of those older than 50 years developed an endothelial infection (40).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the use of the term "mycotic aneurysm" implies a wide spectrum of disease entities including all cases of true or pseudoaneurysms. Most of the patients with mycotic aneurysm due to Salmonella have preexisting atherosclerotic disease at the site of subsequently infected aneurysm (40,105). In a series of patients with bacteremia due to Salmonella, 25% of those older than 50 years developed an endothelial infection (40).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
“…Mycotic aneurysm caused by Salmonella was almost uniformly fatal in previous times; however, multiple publications of case reports and case series found that early surgical intervention has greatly increased survival (3,27,63,105,131,142,150). Most surgeons consider the excision of an infected vessel with extra-anatomic vascular reconstruction to be the surgery of choice for abdominal mycotic aneurysm (142).…”
Section: Clinical Spectrum Of Infectionmentioning
confidence: 99%
“…2,7 Thus, it is not surprising to find that about 25% of patients with Salmonella aortitis have preexisting diabetes mellitus. 7,8 A third form of aortitis is known as microbial aortitis. This type of endovascular infection is associated with seeding of an atherosclerotic wall in the course of bacteremia with formation of a pseudoaneurysm, which lacks normal arterial layers.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A third form of aortitis is known as microbial aortitis. This type of endovascular infection is associated with seeding of an atherosclerotic wall in the course of bacteremia with formation of a pseudoaneurysm, which lacks normal arterial layers.…”
mentioning
confidence: 99%
“…Abdominal examination revealed guarding with severe tenderness in the left lower quadrant, an expanding tender mass 15 x 15 cm in diameter in the left iliac fossa, and weak pulses in the left lower limb. Laboratory investigations revealed a hemoglobin of 8.3 g/dL, white blood cell count 6000/mm 3 , platelet count 38,000/mm 3 , random blood sugar 20.5 mmol/L, serum creatinine 137 μmol/L, blood urea nitrogen 6.3 mmol/L, Na ++ 148 mmol/L, K + 3.3 mmol/L, CO 2 10 mmol/L, calcium 3.08 mmol/L. Chest x-ray was normal.…”
Section: Case Reportmentioning
confidence: 99%